2015
DOI: 10.1002/poc.3403
|View full text |Cite
|
Sign up to set email alerts
|

Designing kinetically stable aryltrifluoroborates as 18F‐capture agents for PET imaging

Abstract: One‐step 18F‐radiolabeling of peptides and other large biomolecules has been challenged by a critical gap in chemical compatibility between fluoride anion, which is unreactive as a nucleophile in water, and large biomolecules such as peptides that are insoluble in dry solvents. Traditionally, this disparity has been overcome through the preliminary synthesis of an 18F‐labeled radioprosthetic group that is appended to peptides following at least one additional step. Ideally, however, peptides should be labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…32 In addition, ortho substituents sterically clash with the fluorine atoms of difluoroborane 5, disfavoring its production and thereby retarding solvolysis of the trifluoroborate. 29 Finally, we found that electron-deficient N-heterocycles significantly retard solvolysis. 33,34 With this understanding, we designed a new EWGsubstituted ArBF 3 − (Figure 6), in which the three fluorine atoms on the ring predictably increased the solvolytic half-life to ∼1000 min while the m-carboxylate enabled bioconjugation via an amide bond, which further enhanced the stability (σ m = 0.28 for −CONH 2 vs −0.1 for −COO − ).…”
Section: Accounts Of Chemical Researchmentioning
confidence: 92%
See 3 more Smart Citations
“…32 In addition, ortho substituents sterically clash with the fluorine atoms of difluoroborane 5, disfavoring its production and thereby retarding solvolysis of the trifluoroborate. 29 Finally, we found that electron-deficient N-heterocycles significantly retard solvolysis. 33,34 With this understanding, we designed a new EWGsubstituted ArBF 3 − (Figure 6), in which the three fluorine atoms on the ring predictably increased the solvolytic half-life to ∼1000 min while the m-carboxylate enabled bioconjugation via an amide bond, which further enhanced the stability (σ m = 0.28 for −CONH 2 vs −0.1 for −COO − ).…”
Section: Accounts Of Chemical Researchmentioning
confidence: 92%
“…We therefore performed a Hammett analysis to quantify the effects of EDGs and EWGs in terms of published σ and σ + values; log­( k solv ) is negatively correlated with the sum of the σ values: ρ ≈ −1 ( R ≈ 0.9) . In addition, ortho substituents sterically clash with the fluorine atoms of difluoroborane 5 , disfavoring its production and thereby retarding solvolysis of the trifluoroborate . Finally, we found that electron-deficient N-heterocycles significantly retard solvolysis. , …”
Section: Designing a Kinetically Stable Arbf3 –mentioning
confidence: 95%
See 2 more Smart Citations
“…It is well-known that boronic acids form covalent bonds with 1,2- or 1,3-diols to generate five- or six-membered cyclic boronic esters under mild and neutral conditions. , Therefore, boronic acids such as phenyl boronic acid and polymer-supported boronic acids have been used as protective or transient masking agents for diols. ,, However, cyclic arylboronic esters, except those derived from highly hindered substrates, are susceptible to hydrolysis, even under neutral conditions. Consequently, this poor stability limits the reaction conditions under which this protective strategy may be applied.…”
mentioning
confidence: 99%